Praziquantel Reduces Maternal Mortality and Offspring Morbidity by Enhancing Anti-Helminthic Immune Responses - Lacorcia, Matthew; Kugyelka, Réka; Spechtenhauser, Lorenz; Prodjinotho, Ulrich Fabien; Hamway, Youssef; Spangenberg, Thomas; da Costa, Clarissa Prazeres (Frontiers in Immunology, 2022)
Alongside the wide distribution throughout sub Saharan Africa of schistosomiasis, the morbidity associated with this chronic parasitic disease in endemic regions is often coupled with infection-driven immunomodulatory processes which modify inflammatory responses. Early life parasite exposure is theorized to drive immune tolerance towards cognate infection as well as bystander immune responses, beginning with in utero exposure to maternal infection. Considering that 40 million women of childbearing-age are at risk of infection worldwide, treatment with Praziquantel during pregnancy as currently recommended by WHO could have significant impact on disease outcomes in these populations. Here, we describe the effects of anthelminthic treatment on parasite-induced changes to fetomaternal cross talk in a murine model of maternal schistosomiasis. Praziquantel administration immediately prior to mating lead to clear re-awakening of maternal anti-parasite immune responses, with persistent maternal immune activation that included enhanced anti-schistosome cytokine responses. Clearance of parasites also improved capacity of dams to endure the additional pressure of pregnancy during infection. Maternal treatment also drove lasting functional alterations to immune system development of exposed offspring. Prenatal anthelminthic treatment skewed offspring immune responses towards parasite clearance and reduced morbidity during cognate infection. Maternal treatment also restored offspring protective IgE antibody responses directed against schistosome antigens, which were otherwise suppressed following exposure to untreated maternal infection. This was further associated with enhanced anti-schistosome cytokine responses from treatment-exposed offspring during infection. In the absence of cognate infection, exposed offspring further demonstrated imprinting across cellular populations. We provide further evidence that maternal treatment can restore a more normalized immune profile to such offspring exposed in utero to parasite infection, particularly in B cell populations, which may underlie improved responsiveness to cognate infection, and support the WHO recommendation of anthelminthic treatment during pregnancy.